2008
DOI: 10.1089/apc.2007.0093
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum of Adverse Events After Generic HAART in Southern Indian HIV-Infected Patients

Abstract: To determine the incidence of clinically significant adverse events after long-term, fixed-dose, generic highly active antiretroviral therapy (HAART) use among HIV-infected individuals in South India, we examined the experiences of 3154 HIV-infected individuals who received a minimum of 3 months of generic HAART between February 1996 and December 2006 at a tertiary HIV care referral center in South India. The most common regimens were 3TC + d4T + nevirapine (NVP) (54.8%), zidovudine (AZT) + 3TC + NVP (14.5%), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
48
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(62 citation statements)
references
References 28 publications
10
48
3
Order By: Relevance
“…The difference may also be attributed to the low use of laboratory diagnosis of hepatoxicity and other ADRs in resource-limited settings. However, our results compare well with those of a retrospective study involving 3154 patients at a tertiary HIV care referral centre in South India which reported hepatitis in 3.5% of patients (24).…”
Section: Discussionsupporting
confidence: 86%
“…The difference may also be attributed to the low use of laboratory diagnosis of hepatoxicity and other ADRs in resource-limited settings. However, our results compare well with those of a retrospective study involving 3154 patients at a tertiary HIV care referral centre in South India which reported hepatitis in 3.5% of patients (24).…”
Section: Discussionsupporting
confidence: 86%
“…Stavudine containing regimens were also associated with more cases of lipid abnormalities. Stavudine-associated peripheral neuropathy has been found in other resource-limited settings which use stavudine based combinations as the first line HAART regimen (15,16,(21)(22)(23) and there have been calls for replacement of stavudine with tenofovir or zidovudine as a first line drug (24).…”
Section: Discussionmentioning
confidence: 99%
“…54 Another study from South India reported a 5.4% incidence of anemia. 50 In SM Curkendall et al, it was reported that 13.0% of patients initiating a ZDVcontaining regimen and 8.7% of those initiating another NRTI containing regimen had anemia's. The non-nucleoside reverse transcriptase inhibitors (NNRTI) are potent antiretroviral agents recommended for use in the treatment of HIV infection.…”
Section: Anemia (Myelo-suppression)mentioning
confidence: 99%
“…[47][48][49] After the therapy initiation, Zidovudine-related anemia usually occurs within 3 months. 50 Risk factors include high zidovudine dosage, increased treatment duration, low CD4 cell count, and preexisting anemia. 51 Studies from 8 Nigeria, Co te d'Ivoire, Haiti, and India have found rates of zidovudine-related anemia of 3%-12%.…”
Section: Anemia (Myelo-suppression)mentioning
confidence: 99%
See 1 more Smart Citation